Effects of Artemisin and Moringa oleifera Extract Combination on CD4+ and CD8+ Percentage of Mice Infected with Plasmodium berghei - BR. Sijabat, Melda Fio Flora; Hernowati, Tinny Endang; Fitri, Loeki Enggar (Journal of Tropical Life Science, 2016)
Â This research aims to examine the effect of Artemisin and Moringa oleifera leaf extract combination on the percentage of CD4+ and CD8+ T cell of mice infected with P.berghei. CD4+ and CD8+ T cells have important role in eliminating Plasmodium intracellular parasite that causes malaria infection. Artemisin is a potent antimalarial that kills the parasite through free radicals production. Excessive free radicals damage the immune cells, including CD4+ and CD8+ T cells. Flavonoid (quercetin and kaempferol) bioactive on Moringa leaves is a powerful antioxidant and anti-inflammatory, and is expected to prevent and decrease the adverse effects of Artemisin. This experimental post-test group research was conducted on six groups, i.e. normal mice (negative control), P.berghei infected mice without treatment (positive control), and four other groups, i.e. P.berghei infected mice and treated with Artemisin 0.004mg/gBW (A), and combinations of Artemisin 0.004mg/gBW and Moringa leaf extract 0.125mg/gBW (DK1), 0.250mg/gBW (DK2), and 0.500mg/gBW (DK3). On day 3 and 7, blood samples from each group were drawn randomly, parasitemia degree was calculated microscopically (magnification 1000 times), the percentage of CD4+ and CD8+ T cells was determined using flowcytometry. The results of this study indicated that the administration of Artemisin and Moringa leaf extract combination for 7 days significant increased the percentage of CD4 + T cells in DK2 (p=0.001) and DK3 (p=0.000), and decreased the degree of parasitemia in DK1 (p=0.000), DK2 (p=0.000), and DK3 (p=0.000), however CD8 + T cells show no difference. There was a relationship between Artemisin and Moringa leaf extract combination with the degree of parasitemia (p=0.000) and the percentage of CD4+ T cells (p = 0.000), but not on CD8+ T cells.Â Keywords: parasitemia, CD4+ and CD8+ T cells, Moringa oleifera